Awareness of Listening Comprehension Importance among Languages Students: A Cross-sectional Study (The International Journal of Educational Sciences and Arts, 2023)
The process of listening comprehension was neglected for years in the English classroom. It was thought to be a passive skill until some authors highlighted its importance in language acquisition and communication. In order to find out the extent to which students are aware of the importance of listening comprehension to learn English, a descriptive study was conducted. To collect the information, a questionnaire was sent to 166 students of language teaching at the Language Faculty of the Universidad Autonoma de Baja California, Mexico, Tijuana. The questionnaire consisted of three parts, the first containing demographic information; the second dealing with the basic principles of listening comprehension; and the third one with information about listening comprehension activities.
Keywords: Listening Comprehension; language students; English Teaching